2010
DOI: 10.1111/j.1747-4477.2010.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength and fracture analysis between resin cements and root canal dentin

Abstract: The aim of this research is to evaluate bond strength between translucent fibre posts (White Post DC, FGM or FRC Postec Plus, Ivoclar/Vivadent) and intraradicular dentin at three different levels (cervical, middle and apical) using a dual-cure (AllCem, FGM) or self-curing (Multilink, Ivoclar/Vivadent) resin cement. Also, the fracture type after push-out test was analysed under SEM. Thirty-two extracted single-root teeth were selected. After undergoing endodontic therapy, they were randomly divided into four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
1
14
0
3
Order By: Relevance
“…Resin cements are recommended for luting anterior monolithic ceramic restorations because of low solubility, better esthetics provided by matching with the ceramic shade, an improved marginal seal, and a high bond strength . Dual‐cure resin cements are favorable materials for the cementation of all‐ceramic restorations because they take advantage of both light‐ and chemical‐cure mechanisms to guarantee adequate and complete polymerization of the material in case of insufficient light activation . However, some investigators state that the two components do not completely interact in all cases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resin cements are recommended for luting anterior monolithic ceramic restorations because of low solubility, better esthetics provided by matching with the ceramic shade, an improved marginal seal, and a high bond strength . Dual‐cure resin cements are favorable materials for the cementation of all‐ceramic restorations because they take advantage of both light‐ and chemical‐cure mechanisms to guarantee adequate and complete polymerization of the material in case of insufficient light activation . However, some investigators state that the two components do not completely interact in all cases .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Dual-cure resin cements are favorable materials for the cementation of all-ceramic restorations because they take advantage of both light-and chemical-cure mechanisms to guarantee adequate and complete polymerization of the material in case of insufficient light activation. [11][12][13][14] However, some investigators state that the two components do not completely interact in all cases. [15][16][17] Previous studies showed that the microhardness of dual-cure resin cements was lower than that of self-cure cements in case of insufficient light activation beneath a ceramic restoration with a 3-mm thickness.…”
mentioning
confidence: 99%
“…[42][43] Post de bonding turned out to be the most frequent failure of endodontic ally treated teeth restored with post and core systems, 44 whereas vertical root fractures were the most serious type of failure. [45][46] Adhesively luted posts revealed improved retention compared to conventionally cemented posts, and thus might reduce the incidence of de bonding 47 ,so in the present study the adhesive resin cement was selected.…”
Section: Discussionmentioning
confidence: 99%
“…18 Post tipinden bağımsız olarak en yüksek bağlanma dayanımının koronal, en düşük bağlanma dayanımının ise apikal bölgede olduğu bildirilmiştir. [18][19][20][21][22] Bu durumun nedenleri arasında post boşluğunun apikal kısmına ulaşma güçlüğü, simanın apikal bölgeye tam olarak uygulanmasındaki zorluklar ve bunlara bağlı mikro boşlukların oluşması ya da o bölgede kök kanal dolgu materyali ve kanal patı artıklarının kalmış olması 18,19,21,[23][24][25][26] , dentin tübül sayısının apikal bölgelere gidildikçe azalması 27 , koronal bölgeye bağlayıcı ajanların daha kolay uygulanması ve polimerizasyon için kullanılan ışık kaynaklarının apikal bölgeye göre bu bölgede daha etkili olabilmesi 28 olarak özetlenebilir. Post restorasyonlarında başarısızlığa yol açabilen bu faktörlerin kökün farklı bölgelerinde değerlendirilmesinin büyük önem taşıması açısından çalışmamızda farklı bağlayıcı yaklaşımların bağlanma dayanım değerleri, kökün farklı bölgelerinde incelendi.…”
Section: Saatlik Ve 1 Aylık öLçümlerin Karşılaştırılmasıunclassified